Pain-related stress during the Neonatal Intensive Care Unit stay and SLC6A4 methylation in very preterm infants - Provenzi, Livio; Fumagalli, Monica; Sirgiovanni, Ida; Giorda, Roberto; Pozzoli, Uberto; Morandi, Francesco; Beri, Silvana; Menozzi, Giorgia; Mosca, Fabio; Borgatti, Renato; Montirosso, Rosario (Frontiers in Behavioral Neuroscience, 2015)
Very preterm (VPT) infants need long-lasting hospitalization in the Neonatal Intensive Care Unit (NICU) during which they are daily exposed to pain-related stress. Alterations of DNA methylation at the promoter region of the SLC6A4 have been associated with early adverse experiences in infants. The main aim of the present work was to investigate the association between level of exposure to pain-related stress during hospitalization and changes in SLC6A4 DNA methylation at NICU discharge in VPT infants. In order to exclude the potential effect of birth status (i.e., preterm vs. full-term birth) on SLC6A4 methylation, we preliminarily assessed SLC6A4 epigenetic differences between VPT and full-term (FT) infants at birth. Fifty-six VPT and thirty-two FT infants participated in the study. The level of exposure to pain-related stress was quantified on the basis of the amount of skin-breaking procedures to which they were exposed. VPT infants were divided in two sub-groups: low-pain exposure (LPE, N = 25) and high-pain exposure (HPE, N = 31). DNA methylation was evaluated at birth for both VPT and FT infants, assessing 20 CpG sites within the SLC6A4 promoter region. The same CpG sites were re-evaluated for variations in DNA methylation at NICU discharge in LPE and HPE VPT infants. No differences in SLC6A4 CpG sites’ methylation emerged between FT and VPT infants at birth. Methylation at CpG sites 5 and 6 significantly increased from birth to NICU discharge only for HPE VPT infants. Findings show that preterm birth per se is not associated with epigenetic alterations of the SLC6A4, whereas higher levels of pain-related stress exposure during NICU stay might alter the transcriptional functionality of the serotonin transporter gene.